ChemInform Abstract: A Simple Method for Desymmetrizing 1, 1′‐Ferrocenedicarboxaldehyde. Issue 49 (9th December 2014) - Benniston, Andrew C.; Sirbu, Dumitru; Turta, Constantin; Probert, Michael R.; Clegg, William
Abstract The dialdehyde (I) can be easily converted into the desymmetrized compound (II) by simple oxidation with KMnO4.